2017
DOI: 10.1016/j.msea.2017.03.102
|View full text |Cite
|
Sign up to set email alerts
|

Development of strength-hardness relationships in additively manufactured titanium alloys

Abstract: A major concern for additively manufactured (AM) Ti-6Al-4V components is how AM processing parameters and post-process heat treatments impact the resulting mechanical behavior. The applicability of using microhardness measurements as a predictive tool for yield and tensile strengths of AM Ti-6Al-4Vwould provide a rapid and useful screening mechanism for ensuring that properties meet requirements in complex geometries. However, microhardness measurements on Ti-6Al-4V exhibit high levels of data variability due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 49 publications
1
40
1
1
Order By: Relevance
“…Despite a similar microstructure in both laser and electron beam DED, the scale of these microstructure characteristics varied depending on the AM process. It was reported that the microstructure of electron beam based DED is coarser with respect to the laser based one [59,82]. Liu et al suggested the development of grain morphology during the direct laser deposition of different geometries ( Figure 2).…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Despite a similar microstructure in both laser and electron beam DED, the scale of these microstructure characteristics varied depending on the AM process. It was reported that the microstructure of electron beam based DED is coarser with respect to the laser based one [59,82]. Liu et al suggested the development of grain morphology during the direct laser deposition of different geometries ( Figure 2).…”
Section: Microstructurementioning
confidence: 99%
“…This specific orientation is explained by the direction of heat conduction during the direct laser deposition [28]. It was found that the different processing and post-process conditions were expected to result in various microstructures and a wide range of mechanical properties [82][83][84]. For instance, the microstructure of components produced by laser or electron beam based DED in as deposited condition exhibited a lamellar α + β structure.…”
Section: Microstructurementioning
confidence: 99%
“…Apart from the application of DED as a coating technique, this technology has intensively been employed as a manufacturing technology [4,42,43]. Over the past decade, DED could attract more attention regarding its capability in the fabrication of parts with complex geometries to near-net-shape, with the high cost and material savings.…”
Section: Directed Energy Deposition (Ded)mentioning
confidence: 99%
“…The addition of Al stabilizes the α phase while V stabilizes β. Generally, as-deposited microstructures after powder bed fusion (PBF) AM exhibit a fine martensitic (α') structure with acicular laths while the microstructures in directed energy deposition (DED) AM typically have a coarser structure consisting of lamellar α and small amounts of β [80]. Figure 18 Figure 19, which shows a decrease in hardness with the coarsening of the lath for DED-L and PBF-EB.…”
Section: Titanium Alloysmentioning
confidence: 99%
“…The works of Tabor [112] and Cahoon [113] have shown that hardness is directly proportional to yield strength. Recently, Keist and Palmer [80] investigated the strength-hardness relationships for the DED of Ti-6Al-4V using both laser and electron beam heat sources. Their correlation is plotted along with independent experimental data for Ti-6Al-4V components fabricated by PBF and DED processes in Figure 20.…”
Section: Grain Sizementioning
confidence: 99%